Singular nonlinear eigenvalue problem for second order differential equation with energy dissipation - Parasyuk, I.O.; Pozur, S.V. (Нелінійні коливання, 2002)
An eigenvalue problem on the half line for a singular nonlinear ordinary differential operator of the second
order is considered. We find sufficient conditions under which this problem has a solution which has a
prescribed number of zeroes and vanishes at infinity. Розглядається задача на власнi значення на пiвосi для нелiнiйного сингулярного звичайного диференцiального рiвняння другого порядку. Знайдено достатнi умови, при яких ця задача має
розв’язок iз заданою кiлькiстю нулiв, що прямує до нуля на нескiнченностi.